Effects of heavy metals in acute ischemic stroke patients: A cross-sectional study. Issue 9 (4th March 2022) - Yen, Cheng-Chang; Chen, Hsin-Hung; Hsu, Yi-Ting; Tseng, Ching-Jiunn; Lin, Ching-Huang
Abstract : Abstract: Cerebrovascular disease is the second commonest cause of mortality globally and among the commonest causes of disability. However, research executed to probe the heavy metal exposure–stroke incidence relationship is scarce. Accordingly, we executed our study to probe the relationship of heavy metal concentrations (ie, concentrations of lead [Pb], mercury [Hg], cadmium [Cd], and arsenic) in the serum and urine of acute ischemic stroke (AIS) patients with several patient variables. For enrollment, we chose patients who had a first AIS within 7 days after the onset of a stroke. Thus, 33 newly diagnosed patients with AIS were recruited. We determined the aforementioned metals' concentrations by executing inductively coupled plasma mass spectrometry. We also gauged the association between such metal concentrations and patient variables by employing Spearman correlation coefficient. To examine the differences in metal concentrations between the different variables, we implemented an independent Mann–Whitney U test. In our cohort analysis, we noted serum Pb and Cd concentrations to be positively correlated with serum creatinine and hemoglobin. Serum and urine Cd concentrations had a negative correlation with impaired HbA1c in AIS patients. Urine Hg had a positive correlation with C-reactive protein in the participants. Participants who smoked or consumed alcohol had significantly higher Pb and Cd levels in serum than did those who neither smoked nor drank. Patients with AIS who smoked or consumed alcohol had high levels of serum Pb and serum Cd than did those who did not. Patients with AIS who consumed alcohol had significantly higher Pb and Hg urine concentrations than did those who did not. Our study indicated that serum Cd and Pb elevation increased the AIS risk in southern Taiwan patients.